The cell walls of different Chara species are characterized by branched galactans rich in 3-O-methylgalactose and absence of AGPs - Pfeifer, Lukas; Mueller, Kim-Kristine; Utermöhlen, Jon Hendrik; Erdt, Felicitas; Zehge, Jean Bastian Just; Schubert, Hendrik; Classen, Birgit (Physiologia Plantarum, 2023)
Streptophyte algae are the closest relatives to land plants; their latest common ancestor performed the most drastic adaptation in plant evolution around 500 million years ago: the conquest of land. Besides other adaptations, this step required changes in cell wall composition. Current knowledge on the cell walls of streptophyte algae and especially on the presence of arabinogalactan-proteins (AGPs), important signalling molecules in all land plants, is limited. To get deeper insights into the cell walls of streptophyte algae, especially in Charophyceae, we performed sequential cell wall extractions of four Chara species. The three species Chara globularis, Chara subspinosa and Chara tomentosa revealed comparable cell wall compositions, with pectins, xylans and xyloglucans, whereas Chara aspera stood out with higher amounts of uronic acids in the pectic fractions and lack of reactivity with antibodies binding to xylan- and xyloglucan epitopes. Search for AGPs in the four Chara species and in Nitellopsis obtusa revealed the presence of galactans with pyranosidic galactose in 1,3-, 1,6- and 1,3,6-linkage, which are typical galactan motifs in land plant AGPs. A unique feature of these branched galactans was high portions of 3-O-methylgalactose. Only Nitellopsis contained substantial amounts of arabinose A bioinformatic search for prolyl-4-hydroxylases, involved in the biosynthesis of AGPs, revealed one possible functional sequence in the genome of Chara braunii, but no hydroxyproline could be detected in the four Chara species or in Nitellopsis obtusa. We conclude that AGPs that is typical for land plants are absent, at least in these members of the Charophyceae.